2003
DOI: 10.1097/01.asn.0000076076.88336.b1
|View full text |Cite
|
Sign up to set email alerts
|

Bias in Assessment of Health-Related Quality of Life in a Hemodialysis Population

Abstract: Abstract. Examined is the relationship of patient-reported health-related quality of life (HRQOL) to the mode of survey administration in the Hemodialysis Study. In addition to selfadministered surveys to assess HRQOL, interviewer-administered surveys were made available to include patients with poor vision, decreased manual dexterity, or strong preference. For examining the predictors of participation by self-administration of the survey, multiple logistic regression was performed. For examining the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 28 publications
0
42
0
1
Order By: Relevance
“…Conversely, patients may have underreported potentially embarrassing symptoms such as erectile dysfunction in the context of face-to-face interviews. Future studies should examine the impact of mode of survey administration on symptom reporting as this variable was found to affect reporting of HRQoL in the HEMO study (46). Third, we used the IEQ to measure HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, patients may have underreported potentially embarrassing symptoms such as erectile dysfunction in the context of face-to-face interviews. Future studies should examine the impact of mode of survey administration on symptom reporting as this variable was found to affect reporting of HRQoL in the HEMO study (46). Third, we used the IEQ to measure HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies 104,[111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] published between 1994 and 2003 used SF-36. Not all studies reported all subscales.…”
Section: Meta-analysis Of Short Form Questionnaire-36 Itemsmentioning
confidence: 99%
“…The impact of the different modes of using SF-36 was assessed using weighted pooled measures of agreement for within-subject comparisons and random-effects meta-analysis for between-subject comparison. There were seven studies 104,111,112,[114][115][116][117] that provided betweensubject comparisons only, eight studies [119][120][121][122][123][124][125][126] that provided within-subject comparisons only and two studies 113,118 that contributed data to both analyses. Table 15 summarises the information available from each study.…”
Section: Meta-analysis Of Short Form Questionnaire-36 Itemsmentioning
confidence: 99%
See 2 more Smart Citations